DYSTOCIA DUE TO EMPHYSEMATOUS DICEPHALIC MONSTER IN A SHE BUFFALO - AGRAWAL, JITENDRA KUMAR; PATEL, AKHIL; VERMA, MEENA; KUMAR, PRAMOD (The Indian Journal of Animal Reproduction, 2023)
A non-descript buffalo suffering with dystocia due to enlarged emphysematous dicephalic monster andits successful management with laparohysterotomy has been discussed.
Keywords: Buffalo; Fetus; Dystocia; Emphysematous; Monster